Chelating Effect of Cellulose Acetate Hydrogel Crosslinked with EDTA Dianhydride Used as a Platform for Cell Growth - Anna Melero; Andre Senna; Juliana Domingues; Adriana Motta; Moema Haussen; Antonio Riul Junior; Eliana Duek; Vagner Botaro (Advances in Materials Science and Engineering)
The use of biomaterials capable of achieving controlled release of drugs or chemical and physical interactions with living organisms causes these new materials to be studied in depth to better target their future applications. An example of this is the use of materials that have in their physical structure elements with chelating effects, capable of interacting with the ions and cations present in the cell culture media, drugs, and other elements capable of interacting with the human body. In this work, cellulose acetate hydrogel (HAC) crosslinked with EDTAD (ethylenediaminetetraacetic acid dianhydride) showed a significant chelating effect capable of altering the adhesion of mesenchymal cells in the first days of in vitro tests. This result became our main question in this work, and by using new cell viability assays, it was verified that the hydrogel interacted with the culture medium, removed the salts present, such as Ca2+ and Mg2+, and promoted a decrease in the amount of cells adhered to the material but not cell death. After saturation of Ca2+ and Mg2+, we obtained an improvement in cell adhesion. Electrochemical impedance spectroscopy (EIS) results also verified the dynamics of linked or mobile loads in the volume and interface regions of HAC-EDTA and the presence of characteristic bands related to the interaction between calcium and magnesium present in the culture medium with HAC-EDTA. The DMA traction test showed that there was no dynamic-mechanical change in the structure of the material at temperatures between 20 and 60°C, which is ideal for this studied biomaterial. The purpose of these tests is to aid in the characterization of future biomaterials, where the physicochemical interaction of some of them is often confused with a false cytotoxicity, which in fact may only be an easily identifiable and adaptable structural feature.